Hemorrhagic cystitis in bone marrow transplant recipients: First report of cases in our country - NUNURA, JUAN (2004)
Objective: To determine the incidence, clinical features and complications of bone marrow transplant-related hemorrhagic cystitis (HC). Material and Methods: Retrospective study of bone marrow transplant patients attended at the Edgardo Rebagliati Martins National Hospital Bone Marrow Transplant Unit from November 1994 to October 2003 and who developed HC. Results: A total of 170 patients underwent hematopoietic cell transplantation. Eight patients developed HC with a cumulative incidence of 4,7%, characterized by mainly late onset hematuria and dysuria. In 4 patients, the HC was severe. Two of the three patients who developed HC twice died. Conclusions: Half of the few patients with HC attended at the Unit developed serious disease and when they had HC for a second time the prognosis was fatal.